Improving Formal Support After Sexual Assault: Recommendations From Survivors Living in Poverty in Canada - Sit, Victoria (Journal of interpersonal violence, 2021)
Despite the extensive and often long-lasting sequelae of sexual assault, a significant majority of survivors do not seek assistance from formal support sources, such as police, medical or mental health professionals, and community-based agencies. While growing attention has been directed toward understanding the help-seeking barriers faced by sexual assault survivors, few studies have explored the experiences of survivors living in poverty and how help-seeking can be improved for this marginalized population. The present study sought to understand these issues from perspectives of survivors themselves. Women sexual assault survivors who self-identified as living in poverty (n = 15) were recruited from community-based agencies in the Greater Toronto Area, and participated in semistructured interviews focused on their personal decisions around help-seeking and broader views on access to and quality of formal assistance. Two research questions were of interest. First, what can be done to encourage service use among survivors living in poverty? Second, what is needed to improve the quality of assistance they receive? Thematic analysis revealed three key themes around which participants’ recommendations centered: (a) increased accessibility of information, (b) improved training for formal support providers, and (c) greater opportunities for empowerment. Practical implications of these findings improving the service utilization rates and experiences of formal help-seeking among marginalized women survivors of sexual assault are discussed.